Cytokeratin intermediate filament expression in benign and malignant breast disease. Issue 1 (January 1995) - Heatley, M; Maxwell, P; Whiteside, C; Toner, P
Abstract : AIM–To carry out a comprehensive study of cytokeratin expression in benign and malignant breast epithelium and breast myoepithelial cells; to examine changes in the cytokeratin profile in malignant and benign epithelium and in carcinomas of increasing histological grade. METHODS–Frozen sections from fibroadenomas (19 cases), fibrocystic disease (19 cases), and infiltrating ductal (68 cases), lobular (seven cases), and mucinous carcinomas (three cases) were examined using a panel of monoclonal antibodies. RESULTS–The luminal epithelium in all fibroadenomas and all cases of fibrocystic disease, as well as tumour cells in most carcinomas, reacted with the specific antibodies to cytokeratins 7, 8, 18, and 19 and to antibodies which included these cytokeratins in their specificities (Cam 5.2, AE1, AE3, RCK102, and LP34). In a few ductal carcinomas none of the tumour cells reacted for cytokeratins 7, 8, or 18. Three ductal carcinomas expressed cytokeratin 14. Only occasional cases expressed cytokeratins 3, 4, 10, and 13. Antibodies which included cytokeratins 5 and 14 in their specificities detected myoepithelial cells less efficiently than antiactin antibodies. CONCLUSION–The cytokeratin profiles in the luminal epithelium in benign breast disease and in tumour cells in most carcinomas are similar in most cases. Some carcinomas, however, are negative for cytokeratins 7, 8, or 18. This may provide a means of predicting the biological behaviour of a histologically borderline lesion.